Formality Analysis of Bureaucracy Performance in Drought Management Effort in North Timor District - Tri Anggraini; Handrianus V M Wula (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
Abstract. Management of bureaucratic formalities will hinder the emergence of change, creativity and innovation in providing public services so that it will have a broad impact on the successful achievement of drought disaster management efforts. Analysis of formalities in the bureaucracy that is intended to be related to basic legal, procedures and operational standards in this drought disaster management effort. This research uses a qualitative research method with observation and interview methods. From the research findings, it was found that the National Disaster Management Agency for regional Disaster Mitigation of Northe Central Easth District drought management did not yet have formalities in the form of basic legal, operational procedures and standards that comprehensively regulate the work system in drought disaster management efforts, both pre-disaster, during the disaster and after the drought occurred. This has an impact on the opportunities and risks for making mistakes in decision making. Therefore, it is necessary to design a clear, simple and transparent legal basis formulation based on information technology by involving stakeholders to develop programs and activities that are more specific in relation to drought disaster management efforts.